Social, Health, and Financial Dimensions of 4ps An In-Depth Study of Beneficiary Perceptions - Prejoles, Llewellyn I. (Silliman Journal, 2025)
The beneficiaries of the Pantawid Pamilyang Pilipino Program, or 4Ps, despite receiving program benefits for a maximum of 13 years, still live in poverty, with 3.82 million, or 90%, of the 4.26 million household beneficiaries affected. Given this, a qualitative approach using in-depth interviews (IDIs) was employed to analyze the social, health, and financial perceptions of the 4Ps beneficiaries in the Municipality of Katipunan, Province of Zamboanga del Norte. Four themes emerged: positive educational and health perceptions, positive social perceptions through role performance, issues of economic sufficiency leading to problems of financial perceptions, and indications of dependency and mental mendicancy among other beneficiaries. Rethinking the voices from the ‘4Ps’ beneficiaries, the paper calls for the government to help further beneficiaries shift from dependency to self-reliance. This can be achieved by enhancing the effectiveness of the Sustainable Livelihood Program (SLP) and other 4Ps initiatives through increased economic opportunities and skills training, livelihood diversification, and a shift in mindset through values formation and empowerment programs.